Understanding social work: preparing for practice - Neil Thompson (United Kingdom: Palgrave Macmillan, 2015)
"Focusing on the challenges of achieving good practice, Understanding Social Work reflects recent developments in social work within the context of contemporary society, law and policy. This popular text continues to offer an excellent foundation for readers for anyone wanting a better understanding of the social work role"--
Keywords: Social Service; Social Work; Social Sciences